INTERNATIONAL ENERGY SUPPLY. THE POLITICAL ECONOMY OF WORLD PETROLEUM - McKie, James W. (American Economic Review, 1974)
World oil is a mixture of economics and politics. Economic factors indicate competition among producers will again become effective provided the consuming nations do not capitulate in advance. Saudi Arabia is the dominant producer. Efforts on the supply side to develop additional reserves will only shift the exhaustion curve toward the present. Exponential growth in consumption has serious long run implications.